Intersectionality and Revictimization of Sexual Violence Victims: A Critique of the Indonesian Criminal Justice System - Syalomitha Febiola; Vinita Susanti (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
This study is motivated by the gap between the normative progress of the Sexual Violence Crime Law (UU TPKS) and the persistent practice of revictimization and secondary victimization against sexual violence victims in Indonesia. This research aims to analyze how the dynamics of intersectionality strengthen the mechanisms of revictimization within the criminal justice system and to identify structural and institutional factors causing the failure to provide sensitive and equitable protection for victims with layered vulnerabilities. The research method employed is a qualitative approach through critical document analysis of laws, court decisions, and literature from a feminist criminology and intersectionality perspective. The findings reveal that victims’ vulnerabilities become increasingly complex when gender intersects with social class, disability, age, economic status, and power relations with the perpetrator, thereby exacerbating secondary victimization during reporting, investigation, prosecution, and trial stages. The study concludes that Indonesia’s criminal justice system remains androcentric and patriarchal, failing to accommodate the layered vulnerabilities of sexual violence victims. Recommendations include procedural reform based on trauma-informed justice, integration of intersectionality in law enforcement training, and strengthening integrated services that are gender- and disability-sensitive.